Idiopathic acquired leukonychia - Neki, Nirankar Singh (Journal of Postgraduate Medical Institute, 2014)
A rare case of 29 years old healthy male patient with persistent progressivetotal whitening of all the finger and toe nails (Idiopathic acquired leukonychia)since the age of 20 years is being presented here. The nail changes were ofgreat concern in terms of social embarrassment to the patient. Idiopathic acquiredleukonychia is a rare chromatic disorder of the nails not associated withother abnormalities and discernible etiology. To the best of our knowledge,probably it is the second case report from India after the first one reportedfrom Mumbai earlier. Hence it is presented here for its rarity